A teoria do sentido em Deleuze - Lopes, Luiz Manoel (Universidade Federal de São Carlos, 2006)
The proposal of this work is to study the theory of sense in Deleuze inserted in the questions that reverberate on the contemporaneous philosophical field. Our route will follow the statements of Deleuze on his book Logic of Sense , especially when he detaches that this theme was thought by three different ways: the first, as lekton, by the Stoics on the III century B.C.; the second, as complexe significable, by Gregori di Rimini, on the XIV century; the third as obektiv, by Meinong, on the XIX century. When Deleuze thinks about his theory of sense, he introduces the sense as event.. Our study will start from the rosen questions by Meinong and how they have their origin on the paradox of the representation without object rosen by Benhard Bozano , which allows us to affirm that such paradox is at the origins of the phenomenology and in the analytic philosophy. The theory of the sense of Deleuze will be presented like being out from these two current contemporaneous philosophies.
Keywords: Ontologia; Filosofia contemporânea; Significado e sentido; Filosofia francesa; Diferença (Filosofia); Transcedental field; Event; Sense; Paradox; Immanence; CIENCIAS HUMANAS::FILOSOFIA